The Impact of Supply Chain Strategy on Real Earnings Quality and Market Added Value - Muljanto Siladjaja; Markonah Markonah (International Journal of Supply Chain Management, 2020)
Abstract The previous researches concluded that, the investor had to pressure on management for improving the earning quality, because it related with predicting the future prospect with high accuracy. This paper presents the impact of applying the supply chain management on the cost management to optimize productivity and decreasing cost which will have a direct impact on the earnings. The supply chain policy has advantages in reducing out the cost of capital, so that this policy could be used as a moderated variables. This research used the moderated multiple regression by collecting all data on the listed company in industry manufacturing from 2015-2017. In calculating the market value, this research used the Model H (Two Stages Model of Growth) in predicting the estimated price, which had fulfilled the minimum tracking signals criteria. The statistical testing shown out the supply chain have the positive impact on real earnings quality and market added value, where the higher earnings quality have made  the investors  decision in estimating the future prospect precisely. The supply chain policy played a critical role in reducing out the pattern of opportunistic behavior, when is a pressure on management in having proclivity to improve the earnings quality. This empirical testing had pointed out that publication financial earnings had been implication of game theory. To support the game theory in publication financial performance, this research had provided  a novelty in estimating investor s action  by providing out the schema of investors perception and accounting information. The supply chain policy had proclivity to give a push on supply chain management in implementing earning management, because management effort in disseminate the positive signal.